Thin-wall sheath cable and rapid forming process thereof

The thin-walled sheathed cable with a cross-linked polyethylene insulating layer and modified nylon sheath addresses the challenge of reducing diameter and thickness while maintaining performance, enabling efficient production and improved mechanical and electrical properties.

CN119207869AActive Publication Date: 2024-12-27GUANGDONG SUIXING CABLES IND

Patent Information

Application Number
CN202411375153.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-27
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Existing thin-walled sheathed cables face challenges in reducing outer diameter and sheath thickness while maintaining electrical and mechanical properties, and achieving efficient and stable production processes.

Method used

A thin-walled sheathed cable composed of a cable core, insulating layer made of flame-retardant cross-linked polyethylene, and outer sheath of modified nylon, utilizing specific material compositions and a rapid prototyping process for efficient molding.

Benefits of technology

The cable achieves a small outer diameter, lightweight design with fast heat dissipation, high current carrying capacity, and improved mechanical and electrical properties, along with efficient production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119207869A_ABST
    Figure CN119207869A_ABST
Patent Text Reader

Abstract

The invention discloses a thin-wall sheath cable and a rapid forming process thereof, and the thin-wall sheath cable comprises a cable core, an insulating layer wrapping the cable core, and a sheath at the outermost layer. Wherein the cable core is formed by twisting a plurality of copper single wires; the insulating layer is made of a flame-retardant cross-linked polyethylene material; the sheath is made of a modified nylon material. Printing marks of the thin-wall sheath cable body are arranged on the insulating surface, the insulating layer and the sheath are extruded in a segmented mode, and the cable is formed at a time. The thin-wall sheath cable has the characteristics of flame retardance, environmental protection, wear resistance, small outer diameter, light weight, fast heat dissipation, large relative current-carrying capacity, easiness in pipe penetrating construction and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cables, and in particular to a thin-wall sheathed cable and a rapid prototyping process thereof. Background Art

[0002] In the field of modern power transmission and communication, cables are key connection components, and their performance is directly related to the stability and safety of the entire system. With the vigorous development of aircraft, drones and other aircraft, the demand for thin-walled sheathed cables is also increasing. The aerospace field has extremely stringent performance requirements for cables. Not only do they require cables to have excellent electrical and mechanical properties, but they also need to reduce the weight and volume of cables as much as possible to improve the load capacity and fuel efficiency of aircraft. In addition, aircraft will face more complex and harsh environmental conditions when flying at high altitudes, such as drastic temperature changes, strong vibrations, radiation and humidity. This requires cables to have excellent temperature resistance, wear resistance, moisture resistance and anti-electromagnetic interference capabilities.

[0003] The application advantages of thin-walled sheathed cables in the aerospace field are significant. First, by reducing the thickness of the insulation layer and the sheath, thin-walled cables can significantly reduce the overall weight of the cable while ensuring electrical safety, thus contributing to the lightweight design of the aircraft. Secondly, the thin-walled sheathed cable has a smaller outer diameter, which helps to optimize the wiring layout inside the aircraft, improve space utilization efficiency, and reduce the difficulty of cable installation in a limited space. In addition, the rapid heat dissipation capability of thin-walled sheathed cables enables them to better adapt to the complex thermal management requirements inside the aircraft and reduce performance degradation and safety hazards caused by increased temperature.

[0004] Despite this, existing thin-walled sheathed cables still face some technical challenges. On the one hand, how to further reduce the outer diameter and sheath thickness of the cable while maintaining electrical and mechanical properties is a difficult problem that needs to be solved urgently. On the other hand, in the production process, achieving an efficient and stable molding process to meet the needs of large-scale production is also a key issue in the research and development of thin-walled sheathed cables. Summary of the invention

[0005] Based on the problems existing in the background technology, the present invention provides a thin-walled sheathed cable and a rapid prototyping process thereof. Compared with conventional cables, the thin-walled sheathed cable of the present invention has a small outer diameter, light weight, is easy to pass through pipes, has fast heat dissipation, has a relatively large current carrying capacity, and is easy to install.

[0006] The present invention is implemented by the following technical solutions:

[0007] On one hand, the present invention discloses a thin-wall sheathed cable, comprising a cable core, an insulating layer covering the cable core and an outermost sheath; wherein the cable core is formed by twisting a plurality of copper single wires; the insulating layer is made of flame-retardant cross-linked polyethylene material; and the sheath is made of modified nylon material.

[0008] Furthermore, the flame retardant cross-linked polyethylene material comprises the following raw materials in parts by weight: 100 parts of low-density polyethylene resin, 6-15 parts of modified ethylene-methyl acrylate copolymer, 2-8 parts of melamine formaldehyde resin, 0.5-1.4 parts of cross-linking agent, 0.8-1.6 parts of nano filler, 0.1-1 parts of antioxidant, and 1-3 parts of lubricant.

[0009] Furthermore, the preparation method of the modified ethylene-methyl acrylate copolymer is specifically as follows: dissolving the ethylene-methyl acrylate copolymer in N-formyl dimethyl amide, adding vinyl triethoxysilane under nitrogen protection, stirring and mixing, heating to 60-70° C., adding initiator azobisisobutyl, the initiator addition is controlled within 2 hours, and after the initiator addition is completed, the stirring reaction is continued for 7-9 hours, chloroform is added, filtered, washed, and dried under vacuum conditions to obtain the modified ethylene-methyl acrylate copolymer.

[0010] Furthermore, the molar ratio of ethylene-methyl acrylate copolymer to vinyl triethoxysilane is (3-8):1, and the mass of the initiator accounts for 0.1-0.3% of the total mass of vinyl triethoxysilane.

[0011] Further, the cross-linking agent is dicumyl peroxide;

[0012] The nano filler is nano magnesium oxide with the surface treated by a silane coupling agent;

[0013] The antioxidant was antioxidant 1010;

[0014] The lubricant is calcium stearate.

[0015] Furthermore, the modified nylon material includes the following raw materials in parts by weight: 0-70 parts of nylon 66, 0-40 parts of nylon 663, 3-6 parts of maleic anhydride grafted EPDM rubber, 5-10 parts of halogen-free flame retardant, 4-6 parts of modified nano-silicon dioxide, 1-3 parts of wear resistance agent, 0.1-1 parts of antioxidant, and 0.2-0.8 parts of lubricant.

[0016] Furthermore, the preparation method of modified nano-silica is specifically as follows: disperse nano-silica in toluene, add γ-aminopropyltriethoxysilane dropwise under nitrogen protection, react at a constant temperature of 80°C for 24 hours, filter, wash, and vacuum dry to obtain substance A; disperse substance A in methanol, add methyl acrylate dropwise under nitrogen protection, react at a constant temperature of 50°C for 72 hours, filter, wash, and vacuum dry to obtain substance B; disperse substance B in methanol, add ethylenediamine dropwise under nitrogen protection, react at a constant temperature of 50°C for 72 hours, filter, wash, and vacuum dry to obtain modified nano-silica.

[0017] Further, the halogen-free flame retardant is Fyro lfl ex RDP;

[0018] The wear-resistant agent is PTFE micropowder;

[0019] The antioxidant was antioxidant 1010;

[0020] The lubricant is calcium stearate.

[0021] Another aspect of the present invention discloses a rapid prototyping process for a thin-walled sheathed cable, comprising the following steps:

[0022] S1. The flame retardant cross-linked polyethylene material raw material low-density polyethylene resin, modified ethylene - methyl acrylate copolymer, melamine formaldehyde resin, mixed uniformly, heated, added cross-linking agent, nano filler, antioxidant, lubricant, mixed uniformly to obtain a mixture A;

[0023] S2. Extruding the mixture A outside the cable core, cooling and molding, and obtaining an insulating layer;

[0024] S3. Printing code on the surface of the insulation layer;

[0025] S4. The modified nylon material raw materials of nylon 6, nylon 66, maleic anhydride grafted EPDM rubber, halogen-free flame retardant, modified nano-silica, wear agent, antioxidant, lubricant according to the ratio into a high-speed mixer and mixed evenly to obtain a mixture B;

[0026] S5. Extrude the mixed material B outside the insulating layer, cool and shape it to obtain a sheath, that is, a thin-walled sheathed cable.

[0027] Furthermore, the thickness of the sheath is 0.1-0.3 mm.

[0028] Beneficial effects of the present invention:

[0029] 1. The printed logo of the thin-walled sheathed cable body of the present invention is on the insulating surface, the insulating layer and the sheath are extruded in sections, and the cable is formed in one step. The thin-walled sheathed cable of the present invention has the characteristics of flame retardancy, environmental protection, wear resistance, small outer diameter, light weight, fast heat dissipation, large relative current carrying capacity, and easy pipe insertion construction.

[0030] 2. The insulating layer of the thin-walled sheathed cable of the present invention is designed based on a flame-retardant cross-linked polyethylene material. By reasonably matching low-density polyethylene resin, modified ethylene-methyl acrylate copolymer, melamine formaldehyde resin, cross-linking agent, nanofiller, etc., it is ensured that the cable still has excellent dielectric properties and mechanical strength when the thickness of the insulating layer is reduced to 70% (or even lower) of conventional products. The modified ethylene-methyl acrylate copolymer achieves further functionalization of the polymer by introducing vinyl triethoxysilane into the basic ethylene-methyl acrylate chain. Vinyl triethoxysilane can not only undergo cross-linking reaction with the active groups in the polymer matrix, but also improve the compatibility between the polymer and the inorganic filler, thereby enhancing the overall performance of the material. The modified ethylene-methyl acrylate copolymer and the cross-linking agent together promote the formation of a cross-linked network between the polymer chains. The formation of the cross-linked network improves the thermal stability, mechanical strength and creep resistance of the material, so that the material can still maintain excellent structural stability under high temperature and stress conditions, and is suitable for use in thin-walled cable sheaths.

[0031] 3. The outer jacket of the thin-walled sheathed cable of the present invention is mainly composed of nylon 6 and nylon 66, and the ratio of the two is that the sheath has good thermal stability and wear resistance while maintaining good mechanical properties. The addition of maleic anhydride grafted EPDM rubber improves the toughness of the nylon material and enhances its impact resistance, which can ensure that even when the sheath is thin, the material can still maintain excellent physical properties and is not easy to crack or wear. Nano-silica is surface-modified (γ-aminopropyltriethoxysilane, methyl acrylate, and ethylenediamine in three steps) to improve the compatibility with the nylon matrix, form a strong interface bonding force, and significantly improve the mechanical strength and wear resistance of the material. The nano effect of nano-silica particles can also enhance the rigidity and heat resistance of the material, while improving the aging resistance of the sheath material. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The accompanying drawings are used to provide further explanation of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0033] Figure 1 This is the appearance of the thin-walled sheathed cable prepared in Example 1. DETAILED DESCRIPTION

[0034] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the following embodiments.

[0035] Example 1

[0036] A rapid prototyping process for a thin-wall sheathed cable comprises the following steps:

[0037] S1. Prepare the following flame retardant cross-linked polyethylene material raw materials by weight: 100 parts of low-density polyethylene resin, 12 parts of modified ethylene-methyl acrylate copolymer, 6 parts of melamine formaldehyde resin, 1.0 parts of cross-linking agent, 1.2 parts of nanofiller, 0.5 parts of antioxidant, and 2 parts of lubricant; mix the low-density polyethylene resin, modified ethylene-methyl acrylate copolymer, and melamine formaldehyde resin in the flame retardant cross-linked polyethylene material raw materials, heat, add the cross-linking agent, nanofiller, antioxidant, and lubricant, mix well, and obtain a mixture A;

[0038] The preparation method of the modified ethylene-methyl acrylate copolymer is specifically as follows: dissolving the ethylene-methyl acrylate copolymer in N-formyl dimethyl amine, adding vinyl triethoxysilane under nitrogen protection, the molar ratio of the ethylene-methyl acrylate copolymer to the vinyl triethoxysilane is 4:1, stirring and mixing, heating to 70°C, dropping an initiator azobisisobutyl, the mass of the initiator accounts for 0.2% of the total mass of the vinyl triethoxysilane, the dropping of the initiator is controlled within 2 hours, and after the dropping of the initiator is completed, the stirring reaction is continued for 8 hours, chloroform is added, filtering, washing, and drying under vacuum conditions to obtain the modified ethylene-methyl acrylate copolymer;

[0039] The cross-linking agent is diisopropylbenzene oxide;

[0040] The nano filler is nano magnesium oxide with the surface treated by a silane coupling agent;

[0041] The antioxidant was antioxidant 1010;

[0042] The lubricant is calcium stearate;

[0043] S2. Extruding the mixture A outside the cable core, cooling and molding, and obtaining an insulating layer;

[0044] The cable core is made of 19 copper wires twisted together, and the diameter of each copper wire is 0.55mm;

[0045] S3. Printing code on the surface of the insulation layer;

[0046] S4. Prepare the following nylon material raw materials by weight: nylon 665 parts, nylon 6635 parts, maleic anhydride grafted EPDM rubber 5 parts, halogen-free flame retardant 8 parts, modified nano-silica 5 parts, wear agent 2 parts, antioxidant 0.5 parts, lubricant 0.6 parts; nylon 6, nylon 66, maleic anhydride grafted EPDM rubber, halogen-free flame retardant, modified nano-silica, wear agent, antioxidant, lubricant in the modified nylon material raw materials are put into a high-speed mixer according to the ratio and mixed evenly to obtain a mixture B;

[0047] The preparation method of modified nano-silica is as follows: dispersing nano-silica in toluene, adding γ-aminopropyltriethoxysilane under nitrogen protection, reacting at 80°C for 24 hours, filtering, washing, and vacuum drying to obtain substance A; dispersing substance A in methanol, adding methyl acrylate under nitrogen protection, reacting at 50°C for 72 hours, filtering, washing, and vacuum drying to obtain substance B; dispersing substance B in methanol, adding ethylenediamine under nitrogen protection, reacting at 50°C for 72 hours, filtering, washing, and vacuum drying to obtain modified nano-silica;

[0048] The halogen-free flame retardant is Fyro lfl ex RDP;

[0049] The wear-resistant agent is PTFE micropowder;

[0050] The antioxidant was antioxidant 1010;

[0051] The lubricant is calcium stearate;

[0052] S5. Extrude the mixed material B outside the insulating layer, cool and shape it to obtain a sheath, that is, a thin-walled sheathed cable.

[0053] The final thin-walled sheathed cable has an insulation layer thickness of 0.575 mm, a sheath thickness of 0.15 mm, and a thinnest point thickness of 0.10 mm.

[0054] Example 2

[0055] The difference between this embodiment and embodiment 1 is that in step S1, the following raw materials of flame-retardant cross-linked polyethylene materials are prepared in parts by weight: 100 parts of low-density polyethylene resin, 10 parts of modified ethylene-methyl acrylate copolymer, 6 parts of melamine formaldehyde resin, 0.8 parts of cross-linking agent, 1.4 parts of nanofiller, 0.5 parts of antioxidant, and 2 parts of lubricant.

[0056] Example 3

[0057] The difference between this embodiment and embodiment 1 is that in step S4, the following nylon material raw materials are prepared in parts by weight: 5 parts of nylon 66, 5 parts of nylon 663, 4 parts of maleic anhydride grafted EPDM rubber, 8 parts of halogen-free flame retardant, 6 parts of modified nano-silica, 2 parts of wear agent, 0.5 parts of antioxidant, and 0.6 parts of lubricant.

[0058] Comparative Example 1

[0059] The difference between this comparative example and Example 1 is that ethylene-methyl acrylate copolymer is directly used in step S1.

[0060] Comparative Example 2

[0061] The difference between this comparative example and Example 1 is that no nanofiller is added in step S1.

[0062] Comparative Example 3

[0063] The difference between this comparative example and Example 1 is that nano-silicon dioxide is directly added in step S4.

[0064] Comparative Example 4

[0065] The difference between this comparative example and Example 1 is that the modification step of nano-silica in step S4 is: dispersing nano-silica in toluene, adding γ-aminopropyltriethoxysilane dropwise under nitrogen protection, reacting at a constant temperature of 80° C. for 24 hours, filtering, washing, and vacuum drying to obtain modified nano-silica.

[0066] Comparative Example 5

[0067] The difference between this comparative example and Example 1 is that maleic anhydride-grafted EPDM rubber is not added in step S4.

[0068] Test Example 1

[0069] This test example tests the performance of the flame-retardant cross-linked polyethylene materials prepared in Example 1-2 and Comparative Example 1-2. The tensile strength and elongation at break are tested with reference to JB / T10437-2004 "Cross-linked Polyethylene Insulation Materials for Wires and Cables"; the Concept80 broadband dielectric and impedance spectrometer is used for testing, the test conditions are 0.1Hz, the test temperature is 20°C, and the relative dielectric constant of the test sample is tested; with reference to Appendix C of GB / T140492008 "Rated Voltage 10kV Overhead Insulated Cables", a xenon lamp climate aging box is used for aging resistance testing, and the tensile strength, elongation at break and dielectric constant after aging for 42d are measured; the specific data are shown in Table 1.

[0070] Table 1

[0071] Group Example 1 Example 2 Comparative Example 1 Comparative Example 2 Tensile strength / MPa 23.4 22.0 19.6 18.7 Aging 42d tensile strength / MPa 22.1 20.9 16.2 14.9 Elongation at break / % 554 536 481 493 Elongation at break after aging for 42 days / % 550 540 467 462 Dielectric constant 2.07 2.11 2.43 2.64 Aging 42d dielectric constant 2.15 2.19 2.67 2.82

[0072] As can be seen from the data in Table 1, the flame-retardant cross-linked polyethylene materials prepared by Examples 1 and 2 of the present invention have good mechanical properties and dielectric properties while reducing the thickness of the insulating layer. The introduction of modified ethylene-methyl acrylate copolymer, melamine formaldehyde resin and nanofiller forms a more dense cross-linked network inside the material, which improves the tensile strength of the material. In particular, the modification of vinyl triethoxysilane not only improves the mechanical properties of the copolymer, but also enhances the overall strength of the material through interaction with the nanofiller. The introduction of modified ethylene-methyl acrylate copolymer significantly improves the polarity uniformity of the material, and in particular, the silanization of vinyl triethoxysilane reduces the dielectric loss of the material and the dielectric constant tends to be stable. The addition of nanofiller further improves the insulation of the material, so that the rate of decline of the dielectric constant is slower during the aging process. In Comparative Example 1, unmodified ethylene-methyl acrylate copolymer is directly used. Due to its poor compatibility with the low-density polyethylene matrix, the cross-linked network is not as dense as the modified copolymer, so the tensile strength will be lower. Due to the poor compatibility of unmodified ethylene-methyl acrylate copolymer with the matrix, the polar group distribution is uneven, resulting in a higher dielectric constant, and being easily affected by the electric field during the aging process, the dielectric constant significantly increases. In Comparative Example 2, nanofillers are not used, resulting in a significant reduction in the strength and toughness of the material, and fillers can improve the mechanical properties of the material, and Comparative Example 2 lacking fillers will perform poorly in tensile strength and elongation at break. Due to the lack of nanofillers, its insulation performance is reduced, resulting in a higher dielectric constant, and faster decline during the aging process.

[0073] Test Example 2

[0074] This test example tests the properties of the nylon materials prepared in Example 1, Example 3 and Comparative Examples 3-5. The tensile strength and elongation at break are tested in accordance with GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets"; the wear resistance is tested in accordance with GB / T 3960-2016 "Test methods for sliding friction and wear of plastics". The test results are shown in Table 2.

[0075] Table 2

[0076]

[0077]

[0078] It can be seen from the data in Table 2 that the nylon sheath prepared by the present invention not only has good tensile strength and elongation at break, but also has excellent wear resistance. In Comparative Example 3, nano-silicon dioxide is directly added, and its interface bonding force with the nylon matrix is ​​poor, and interface defects are easily formed, resulting in a significant decrease in the tensile strength of the material. Due to the large rigidity of nano-silicon dioxide particles, unmodified nano-silicon dioxide will reduce the toughness of the material, so the elongation at break also decreases. Although nano-silicon dioxide has the potential to enhance wear resistance, due to the poor bonding force with the matrix, the improvement in wear resistance is limited. In Comparative Example 4, only aminopropylated modified nano-titanium dioxide is used, and its material performance is significantly better than that in Comparative Example 3, but not as good as Examples 1 and 3. Maleic anhydride grafted ethylene propylene rubber is not used in Comparative Example 5. Maleic anhydride grafted ethylene propylene rubber is used as a toughening agent. After not adding it, the various properties of the material are significantly reduced. Especially when the sheath material is thin, the risk of cracking and breakage can be reduced. The invention adopts three-step modification to nano silicon dioxide. The first step is aminopropylation modification to introduce amino groups, thereby enhancing the surface polarity of nano silicon dioxide, making it more compatible with nylon and increasing the interface strength. The second step is acrylate methylation. Methyl acrylate undergoes nucleophilic addition reaction with amino groups through its carboxyl part to form ester bonds, thereby introducing acrylate groups on the surface of nano silicon dioxide. The acrylate groups also have good compatibility with nylon groups, and acrylate has high reactivity, which is helpful for subsequent chemical reactions with other functional groups or substrates, thereby improving the overall mechanical properties of the material. The third step is ethylenediamine modification. Amino functional groups are introduced through cross-linking reaction between acrylate groups and amino groups of ethylenediamine. The presence of amine groups helps to further enhance the compatibility between nano silicon dioxide and nylon substrates, forming stronger interface bonding. The nano silicon dioxide after ethylenediamine has better dispersibility and mechanical strengthening effect. The amine groups can also form hydrogen bonds or chemical bonds with polymer chains, thereby enhancing the tensile strength and elongation at break of the material.

[0079] Example 4

[0080] In the process of manufacturing the cable described in any one of embodiments 1-3, based on the cable encapsulation length, multiple collection starting points and collection end points of the cable are determined, and an insulation layer data set and a sheath data set are established;

[0081] After the insulation layer or the sheath coating is completed, the insulation layer coated cable radius and the sheath coated cable radius of the current detection cable segment are respectively collected at a preset interval with the collection starting point as the starting point and the collection end point as the end point;

[0082] The insulation layer coated cable radius and the sheath coated cable radius are respectively compared with their corresponding initial cable radius to obtain the insulation layer measurement thickness and sheath measurement thickness at each collection point;

[0083] The measured thickness of the insulation layer is sent to the insulation layer data set, and the measured thickness of the sheath is sent to the sheath data set for temporary storage;

[0084] At the same time, the latest data in the insulation layer data set and the sheath data set are compared with the preset thinnest value;

[0085] If the latest data in the insulation layer data set and the sheath data set are both greater than or equal to the preset thinnest value, the current detected cable segment is determined to be qualified, and the latest data in the insulation layer data set is compared with the preset insulation layer thickness to obtain the insulation layer error. When the insulation error is greater than the first preset value, the insulation layer error count is increased by 1;

[0086] Compare the latest data of the sheath data set with the preset sheath thickness to obtain a sheath layer error, and when the sheath layer error is greater than a second preset value, the sheath layer error count is increased by 1;

[0087] Based on the insulation layer error counting result, determine the first error counting frequency corresponding to the acquisition point on the insulation layer of the current detection cable segment, and based on the insulation layer error counting result, determine the second error counting frequency corresponding to the acquisition point on the sheath layer of the current detection cable segment;

[0088] When the first error counting frequency or the second error counting frequency is greater than a preset frequency threshold, an extrusion speed adjustment instruction is sent to the control end;

[0089] Otherwise, continue with the test;

[0090] If the latest data in the insulation layer data set or the sheath data set is less than the preset thinnest value, the current detection cable segment is judged to be unqualified, the current acquisition point is used as the imperfect end point to replace the acquisition end point, and the packaging unqualified information is generated based on the acquisition starting point and the imperfect end point and sent to the control end for display.

[0091] In this embodiment, the cable packaging length refers to the length of a roll of cable in the packaging stage, for example, 100m, 200m, 500m, etc., which can be flexibly set according to actual production needs.

[0092] In this embodiment, the initial cable radius refers to the radius of a bare wire without an insulating layer or the radius of a cable without a protective sheath.

[0093] In this embodiment, the insulation layer data set refers to a data set that stores all the insulation layer measurement thickness data corresponding to each encapsulated cable segment, and the sheath data set refers to a data set that stores all the sheath measurement thickness data corresponding to each encapsulated cable segment. Each encapsulated cable segment corresponds to an insulation layer data set and a sheath layer data set. When a new collection starting point is detected, the corresponding insulation layer data set or sheath layer data set is automatically generated. After the collection end point data is detected, the system will automatically upload the data in the insulation layer data set and the sheath layer data set to the cloud, and then delete the insulation layer data set and the sheath layer data set.

[0094] The preset interval refers to the interval at which the collection points are set, for example, 0.05m, 0.1m, 0.5m, etc., which can be flexibly set according to detection requirements.

[0095] In this embodiment, the first preset value is less than the absolute value of the ratio of the difference between the expected insulation layer thickness and the thinnest value to the expected insulation layer thickness (that is, the preset insulation layer thickness, which can be flexibly set according to production requirements); the second preset value is less than the absolute value of the ratio of the expected sheath thickness (that is, the preset sheath thickness, which can be flexibly set according to production requirements) and the thinnest value difference to the expected sheath thickness.

[0096] In this embodiment, the insulation layer error refers to the absolute value of the ratio between the difference between the measured insulation layer thickness and the preset insulation layer thickness and the preset insulation layer thickness; the sheath layer error refers to the absolute value of the ratio between the difference between the measured sheath thickness and the preset sheath thickness and the preset sheath thickness.

[0097] In this embodiment, the first error counting frequency refers to the ratio of the insulation layer error count value of the current detected cable segment to the total collection points of the current detected cable segment; the second error counting frequency refers to the ratio of the sheath layer error count value of the current detected cable segment to the total collection points of the current detected cable segment.

[0098] The beneficial effects of the above technical solution: during the cable manufacturing process, the present invention divides the cable into segments according to the encapsulation length of the cable, determines the data collection starting point and end point of the corresponding cable segment for each detection, and performs equidistant data collection with the collection starting point as the non-starting point and the collection end point as the non-end point, to obtain the insulation layer coated cable radius and the sheath coated cable radius of the current detected cable segment, and compare them with the corresponding initial cable radius, obtain the insulation layer measurement thickness and the sheath measurement thickness of each collection point, and temporarily store them in the insulation layer data set and the sheath data set corresponding to the current detected cable segment, and compare the latest data in the insulation layer data set and the sheath data set with the preset thinnest value, respectively, and judge whether the current detected electrical segment is qualified according to the comparison result, so as to ensure that the thickness of the protective layer (including the insulation layer and the sheath layer) of the cable product is greater than the thinnest value, realize the protection layer detection of the whole cable, and provide a basis for the encapsulation of the cable. At the same time, when the current detected cable segment is qualified, the insulation layer number The latest data in the data set is compared with the preset insulation layer thickness to obtain the insulation layer error. When the insulation error is greater than the first preset value, the insulation layer error count is increased by 1; the latest data in the sheath data set is compared with the preset sheath thickness to obtain the sheath layer error. When the sheath layer error is greater than the second preset value, the sheath layer error count is increased by 1; based on the insulation layer error counting result, the first error counting frequency corresponding to the acquisition point on the insulation layer of the current detection cable segment is determined, and at the same time, based on the insulation layer error counting result, the second error counting frequency corresponding to the acquisition point on the sheath layer of the current detection cable segment is determined; when the first error counting frequency or the second error counting frequency is greater than the preset frequency threshold, an extrusion speed adjustment instruction is sent to the control end to achieve the purpose of real-time correction of subsequent cable manufacturing according to the real-time manufacturing situation of the current cable, which can minimize the error of the cable protective layer thickness, improve the subsequent cable manufacturing accuracy and cable quality, and improve the safety of the cable in use.

[0099] Example 5

[0100] On the basis of Embodiment 4, when the first error counting frequency or the second error counting frequency is greater than a preset frequency threshold, sending an extrusion speed adjustment instruction to the control end includes:

[0101] When the first error counting frequency is greater than the preset frequency threshold, the insulation layer errors corresponding to all the acquisition points in the insulation layer data set corresponding to the current detected cable segment are obtained, the average error of the insulation layer of the current detected cable segment is calculated, and the counted insulation layer errors are clustered to obtain the first large error set, and the average value of the first large error is calculated;

[0102] Based on the average value of the first large error and the average error of the insulation layer of the current detected cable segment, a first error large fluctuation index is obtained, and combined with the insulation layer error counting frequency and the floating direction of each insulation layer error, a first positive error large fluctuation index and a first negative error large fluctuation index of the insulation layer of the current detected cable segment are determined respectively;

[0103] Based on the first positive error large fluctuation index and the first negative error large fluctuation index, the average error of the insulation layer of the cable segment is corrected to obtain a first error to be calibrated of the insulation layer of the currently detected cable segment;

[0104] Based on the corresponding relationship between the thickness of the mixture A and the extrusion speed, combined with the current extrusion speed and the first error to be calibrated, an adjustment strategy for the extrusion speed of the mixture A is determined, and a first extrusion speed adjustment instruction is generated and sent to the control end;

[0105] When the second error counting frequency is greater than the preset frequency threshold, the sheath layer errors corresponding to all the acquisition points in the sheath data set corresponding to the current detected cable segment are obtained, the average error of the sheath layer of the current detected cable segment is calculated, and the counted sheath layer errors are clustered to obtain the second large error set, and the average value of the second large error is calculated;

[0106] Based on the average value of the second large error and the average error of the insulation layer of the current detected cable segment, the second error large fluctuation index is obtained, and combined with the insulation layer error counting frequency and the floating direction of each sheath layer error, the second positive error large fluctuation index and the second negative error large fluctuation index of the insulation layer of the current detected cable segment are determined respectively;

[0107] Based on the second positive error large fluctuation index and the second negative error large fluctuation index, the average error of the sheath layer of the cable segment is corrected to obtain the second error to be calibrated of the insulation layer of the currently detected cable segment;

[0108] Based on the corresponding relationship between the thickness of the mixture B and the extrusion speed, combined with the current extrusion speed and the second error to be calibrated, the adjustment strategy of the extrusion speed of the mixture B is determined, and the second extrusion speed adjustment instruction is generated and sent to the control end.

[0109] In this embodiment, the first significant error set refers to a data set consisting of insulation layer errors counted in the current detection cable segment; the second significant error set refers to a data set consisting of sheath layer errors counted in the current detection cable segment.

[0110] In this embodiment, the average value of the first large error refers to the average value of the insulation layer errors included in the first large error set, and the average value of the second large error refers to the average value of the insulation layer errors included in the second large error set.

[0111] In this embodiment, the first error large fluctuation index refers to the ratio of the difference between the average value of the first large error and the average error of the insulation layer of the current detected cable segment to the average error of the insulation layer of the current detected cable segment. The second error large fluctuation index refers to the ratio of the difference between the average value of the second large error and the average error of the sheath layer of the current detected cable segment to the average error of the sheath layer of the current detected cable segment.

[0112] In this embodiment, the first positive error large fluctuation index refers to the product of the large insulation layer error count frequency corresponding to the insulation error where the difference between the measured insulation layer thickness and the preset insulation layer thickness is greater than 0 and the first error large fluctuation index. The second positive error large fluctuation index refers to the product of the insulation layer error count frequency corresponding to the large insulation error where the difference between the measured insulation layer thickness and the preset insulation layer thickness is less than 0 and the first error large fluctuation index;

[0113] Among them, the first positive error large fluctuation index is positive; the first positive error large fluctuation index is negative.

[0114] In this embodiment, the second positive error large fluctuation index refers to the product of the large sheath layer error count frequency corresponding to the insulation error when the difference between the measured sheath thickness and the preset sheath thickness is greater than 0 and the second error large fluctuation index. The second positive error large fluctuation index refers to the product of the insulation layer error count frequency corresponding to the large sheath layer error when the difference between the measured sheath thickness and the preset sheath thickness is less than 0 and the second error large fluctuation index;

[0115] Among them, the second positive error large fluctuation index is positive; the second positive error large fluctuation index is negative.

[0116] In this embodiment, the first error to be calibrated refers to the product of the sum of the first positive error large fluctuation index and the first negative error large fluctuation index and the average error of the insulation layer of the cable segment.

[0117] In this embodiment, the second error to be calibrated refers to the product of the sum of the second positive error large fluctuation index and the second negative error large fluctuation index and the average error of the sheath layer of the cable segment.

[0118] The beneficial effects of the above counting scheme are as follows: when the first error counting frequency or the second error counting frequency is greater than the preset frequency threshold, the present invention determines the probability of a large fluctuation in the manufacturing thickness error of the insulation layer or sheath of the current detected cable section (i.e., the first error large fluctuation index or the second error large fluctuation index) according to the difference between the average error of the insulation layer or sheath layer and the average value of the counted large errors, and then determines the positive error large fluctuation index and the negative error large fluctuation index according to the fluctuation distribution of the large errors in the positive and negative directions, and then corrects the average error according to the positive error large fluctuation index and the negative error large fluctuation index to determine the final error (i.e., the error to be calibrated), and determines the adjustment strategy of the extrusion speed of the mixture according to the corresponding relationship between the thickness of the mixture and the extrusion speed, combined with the current extrusion speed and the final error, generates a corresponding extrusion speed adjustment instruction, and sends it to the control end to control the extrusion construction to complete the extrusion speed adjustment, so that the correction of the extrusion speed is in line with the actual situation, ensuring that the cable manufacturing after the extrusion speed adjustment is closer to expectations, and providing a reliable basis for automatic correction in the cable manufacturing process.

[0119] Finally, it should be noted that the above-mentioned embodiments only express several implementation methods of the present invention and are not intended to limit the invention. For those skilled in the art, any modification, equivalent replacement, improvement, etc. made without departing from the concept of the present invention should be included in the protection scope of the invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A thin-walled sheathed cable, characterized in that: It includes a cable core, an insulating layer covering the cable core and an outermost sheath; wherein the cable core is formed by twisting a plurality of copper single wires; the insulating layer is made of flame-retardant cross-linked polyethylene material; and the sheath is made of modified nylon material.

2. The thin-walled sheathed cable according to claim 1, characterized in that: The flame retardant cross-linked polyethylene material comprises the following raw materials in parts by weight: 100 parts of low-density polyethylene resin, 6-15 parts of modified ethylene-methyl acrylate copolymer, 2-8 parts of melamine formaldehyde resin, 0.5-1.4 parts of cross-linking agent, 0.8-1.6 parts of nano filler, 0.1-1 parts of antioxidant and 1-3 parts of lubricant.

3. The thin-walled sheathed cable according to claim 2, characterized in that: The preparation method of the modified ethylene-methyl acrylate copolymer is specifically as follows: dissolving the ethylene-methyl acrylate copolymer in N-formyl dimethyl amide, adding vinyl triethoxysilane under nitrogen protection, stirring and mixing, heating to 60-70° C., dropping an initiator azobisisobutyl, and controlling the dropping of the initiator to be within 2 hours. After the dropping of the initiator is completed, stirring and reacting for 7-9 hours, adding chloroform, filtering, washing, and drying under vacuum conditions to obtain the modified ethylene-methyl acrylate copolymer.

4. The thin-walled sheathed cable according to claim 3, characterized in that: The molar ratio of ethylene-methyl acrylate copolymer to vinyl triethoxysilane is (3-8):1, and the mass of the initiator accounts for 0.1-0.3% of the total mass of vinyl triethoxysilane.

5. The thin-walled sheathed cable according to claim 2, characterized in that: The cross-linking agent is dicumyl peroxide; The nano filler is nano magnesium oxide with the surface treated with a silane coupling agent; The antioxidant was antioxidant 1010; The lubricant is calcium stearate.

6. The thin-walled sheathed cable according to claim 1, characterized in that: The modified nylon material comprises the following raw materials in parts by weight: nylon 660-70 parts, nylon 6630-40 parts, maleic anhydride grafted EPDM rubber 3-6 parts, halogen-free flame retardant 5-10 parts, modified nano silicon dioxide 4-6 parts, wear-resistant agent 1-3 parts, antioxidant 0.1-1 parts, and lubricant 0.2-0.8 parts.

7. The thin-walled sheathed cable according to claim 6, characterized in that: The preparation method of modified nano-silica is specifically as follows: disperse nano-silica in toluene, add γ-aminopropyltriethoxysilane dropwise under nitrogen protection, react at a constant temperature of 80°C for 24 hours, filter, wash, and vacuum dry to obtain substance A; disperse substance A in methanol, add methyl acrylate dropwise under nitrogen protection, react at a constant temperature of 50°C for 72 hours, filter, wash, and vacuum dry to obtain substance B; disperse substance B in methanol, add ethylenediamine dropwise under nitrogen protection, react at a constant temperature of 50°C for 72 hours, filter, wash, and vacuum dry to obtain modified nano-silica.

8. The thin-walled sheathed cable according to claim 6, characterized in that: The halogen-free flame retardant is Fyrolflex RDP; The wear-resistant agent is PTFE micropowder; The antioxidant was antioxidant 1010; The lubricant is calcium stearate.

9. A rapid prototyping process for a thin-walled sheathed cable as claimed in claims 1 to 8, characterized in that: The following steps are involved: S1. The flame retardant cross-linked polyethylene material raw material low-density polyethylene resin, modified ethylene - methyl acrylate copolymer, melamine formaldehyde resin, mixed uniformly, heated, added cross-linking agent, nano filler, antioxidant, lubricant, mixed uniformly to obtain a mixture A; S2. Extruding the mixture A outside the cable core, cooling and molding, and obtaining an insulating layer; S3. Printing code on the surface of the insulation layer; S4. The modified nylon material raw materials of nylon 6, nylon 66, maleic anhydride grafted EPDM rubber, halogen-free flame retardant, modified nano-silica, wear agent, antioxidant, lubricant according to the ratio into a high-speed mixer and mixed evenly to obtain a mixture B; S5. Extrude the mixed material B outside the insulating layer, cool and shape it to obtain a sheath, that is, a thin-walled sheathed cable.

10. The rapid prototyping process for thin-walled sheathed cables according to claim 9, characterized in that: The thickness of the sheath is 0.1-0.3 mm.

Citation Information

Patent Citations

  • X-ETFE (crosslinked ethylene-tetrafluoroethylene) insulating wire or cable with spiral stripe identifications for aerospace and preparation process for insulating wire or cable

    CN102723135A

  • Multi-component compound modified nylon 6 composite material for carrier roller and preparation method thereof

    CN103467978A

  • Heat-conducting wire cable electric-insulation material or sheath material

    CN104017267A

  • Preparation method of nano-silica grafted hyperbranched polyamide

    CN107814948A

  • Nylon 6 composite material and preparation method thereof

    CN109836813A

Cited By

  • Wind power generation cable and preparation method thereof

    CN120757895A